An intracardial mass in a young Syrian refugee. (6th July 2015) - Ingimarsdóttir, Inga Jóna; Wikström, Gerhard
Abstract : A 35-year-old previously healthy man presented with orogenital ulcerations, high fever, weight loss and leg thrombosis. Antibiotics were ineffective. His symptoms persisted and 3 years later he suffered from exertional dyspnoea. Inflammatory markers were elevated and all cultures were negative. CT of the thorax showed bilateral pulmonary embolism and a mass attached to the septum of the right ventricle, as well as an occluded vena cava inferior. Histology of the cardiac mass revealed a thrombus. The pulmonary embolisation progressed despite treatment with full-dose dalteparin. After being diagnosed with Behçet's disease, a multisystemic large-vessel vasculitis, and treated with high-dose prednisolone and cyclophosphamide, his ulcerations and his symptoms of dyspnoea disappeared.